Pengaruh Inklusi Keuangan, Pembiayaan Peer to Peer Lending (P2P) dan Non Performing Finance (NPF) terhadap Profitabilitas Bank Umum Syariah di Indonesia Periode 2016-2023 - Nur Chalizzah; Tenny Badina; Ahmad Fathoni (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
This study aims to see the variables of Financial Inclusion, Peer to Peer Lending (P2P) Financing and Non Performing Financing (NPF) in influencing Profitability. The population in this study is all Islamic Commercial Banks registered with the Financial Services Authority for the 2016-2023 period. The data used in this study is panel data from 8 selected Islamic commercial banks, with a total sample of 32. The sampling technique uses Purposive Sampling. The analysis technique uses the panel data regression method processed using Eviews 12. 0. The results of the study partially show that Third Party Funds (TPF) and the Number of Offices have a positive and significant effect on the profitability of Islamic commercial banks. While Financing, P2P Lending Financing and Non Performing Financing (NPF) have a positive and insignificant effect on the profitability of Islamic commercial banks. The results of the study simultaneously show that the variables of third party funds, number of offices, financing, P2P lending financing and non performing financing have an effect on the profitability of Islamic commercial banks